A Proxy Bidding Mechanism that Elicits all Bids in an English Clock Auction Experiment - Dirk Engelmann; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
This paper reconsiders experimental tests of the English clock auction. We point out why the standard procedure can only use a small subset of all bids, which gives rise to a selection bias. We propose an alternative yet equivalent format that makes all bids visible, and apply it to a 'wallet auction' experiment. Finally, we test the theory against various alternative hypotheses, and compare the results with those that would have been obtained if one had used the standard procedure. Our results confirm that the standard tests are subject to a significant selection bias.
urn:nbn:de:bvb:19-epub-13512-3
Keywords: D44; D45; C91; 330; English Clock Auctions; Experimental Economics